KESIAGAAN PUSTAKAWAN DALAM MENGHADAPI BENCANA KEBAKARAN DI PERPUSTAKAAN UNIVERSITAS BUNG HATTA - Firamida Yuniar (CV. ADIBA ASIHA AMIRA, 2023)
The purpose of this study is to find out how librarians are prepared to face a fire disaster (Disaster Planning) at the Bung Hatta University Library. Various things can be a threat to collections or assets in the library both from damage such as floods, earthquakes, volcanic eruptions, tsunamis, fires and others. Other threats can be caused by biological and chemical factors as well as humans, such as theft, vandalism or the like. This study uses qualitative research methods, namely research that describes phenomena, interviews, observations and documentation. The problems that exist in qualitative research are still temporary, and will develop or after researchers go into the field. This qualitative research requires data sources from informants. The use of the triangulation technique was carried out to test the credibility of the data by checking the data to the same source using different techniques. Such as data obtained from interviews, then checked by observation, and finally documentation. Careful planning of librarians in dealing with disasters will reduce the impact that occurs, including preparedness and actions for long-term risk reduction. The results of this research can theoretically contribute to the body of knowledge for the librarians of Bung Hatta University in dealing with disasters (disaster planning) in the library. Apart from that, it becomes input or recommendation and thoughts for the Bung Hatta University Library